‘A chain of deep-laid and premeditated villainy’: The Roman Catholic Culture of Conspiracy from the Abbé de Barruel to Radical Traditionalism - Doherty, Bernard (Journal for the Academic Study of Religion, 2022)
The flurry of recent interest in what scholars have dubbed ‘conspirituality’ has focused attention on the intersection between conspiracy theories and the overlapping subcultures of New Age, alternative, and esoteric spirituality. These important insights have also highlighted the extensive histories of cultures of conspiracy which exist within larger religious traditions and the related question of why adherents of specific varieties of religion appear to be highly susceptible to strains of conspiracist thinking. To further illustrate the ubiquity of conspiracy theory in contemporary spirituality, this article offers a historical overview of the intricate culture of conspiracy which has developed in the Roman Catholic Church since at least the French Revolution by outlining its five major permutations: anti-Masonry, antisemitism, anti-communism, anti-Satanism and anti-modernism. This article demonstrates the centrality of conspiracy theories in how a sizeable portion of Roman Catholics have responded to what they perceive as the threatening aspects of modernity as well as the renewed popularity of conspiracy theories within a Roman Catholic spiritual milieu during Pope Francis’s papacy.